Marriage, Motherhood, and Self-Blame: Analyzing the Tragic Heroine’s Spiritual Suicide in Jude the Obscure - Javier, Wenona Bea (Journal of Language and Literature, 2024)
The societal phenomenon of self-blame disproportionately impacts women who encounter tragedies as wives and mothers. This is demonstrated in Jude the Obscure (1896) by Thomas Hardy, one of the most controversial pieces in Victorian literature. With the use of textual analysis and the application of feminist theory concentrating on Clarissa Pinkola Estes' idea of the female psychic slumber in her book Women Who Run With the Wolves (1995), this paper inspects Hardy's character of the enigmatic Sue Bridehead, aiming to unearth the underlying causes of her spiritual suicide after the three children’s death. Estes’ notion of spiritual demise indicates a woman’s submission to conventionality after encountering tragedy, especially during marriage and motherhood. As a nonconformist within a traditional societal framework, Sue’s transformation from Part III to VI of the book stands out as she shifts from being a free spirit to a conventional wife after encountering tribulations. Her spiritual suicide stems from three interrelated factors: Regret for her children’s short life; culpability; and her idea that it is God’s way of punishing her for her nonconformist beliefs. This convergence weaves together a memorable picture of a woman's spiritual self-destruction amidst traumatic events and the expectations of a conventional society that women should submit to their husbands and renounce whatever unorthodox beliefs they have.